1991
DOI: 10.1111/j.1439-0442.1991.tb01015.x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Evidence for a Link between Bronchopneumonia and Disseminated Focal Nephritis in Pigs

Abstract: Summary An investigation on the occurrence of different pneumonia types and their possible concurrence with other pluck organ disorders was made on 6,565 pigs presented at slaughter. The frequency of disseminated focal nephritis in a bronchopneumonia group and a non‐bronchopneumonia residual group, respectively, was found to differ significantly from the mean frequency of nephritis in all pig plucks examined. The number of lesioned kidneys in each of 28 samples contributing to the bronchopneumonia group and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Pericarditis has previously been found in association with porcine bronchopneumonia (Buttenschon 1991;Christensen & Enoe 1999), but a high frequency of cultivation of P. multocida from the pericardial sac has not been reported (Buttenschon et al 1997). In this study pericarditis was found in 18 out of the 114 cases of bronchopneumonia with positive cultivation of P. multocida.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…Pericarditis has previously been found in association with porcine bronchopneumonia (Buttenschon 1991;Christensen & Enoe 1999), but a high frequency of cultivation of P. multocida from the pericardial sac has not been reported (Buttenschon et al 1997). In this study pericarditis was found in 18 out of the 114 cases of bronchopneumonia with positive cultivation of P. multocida.…”
Section: Discussionmentioning
confidence: 48%
“…The findings of pericarditis and positive cultivation of P. multocida from the pericardial sac indicate that bronchopneumonia associated with P. multocida is a part of a more complex disease pattern affecting other organ systems in addition to the respiratory tract. In the study by Buttenschon (1991), a connection between bronchopneumonia and cases of focal or diffuse nephritis at the gross level was observed.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations